2015
DOI: 10.1373/clinchem.2014.230615
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Reverse Transcription Step: Practical Implications

Abstract: BACKGROUND:The reverse transcription (RT) of RNA to cDNA is a necessary first step for numerous research and molecular diagnostic applications. Although RT efficiency is known to be variable, little attention has been paid to the practical implications of that variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 39 publications
4
57
0
Order By: Relevance
“…The experiments here suggest that qRT-PCR has lower intra- and inter-assay variation compared to QT-NASBA. The higher precision of qRT-PCR is evident for the entire range of gametocyte densities used in the dilution series, despite involving extra reaction steps, such as DNase treatment and cDNA production, which are known to be a source of variation [27]. These two steps were performed once for each dilution series density, for the three different NF54 cultures and the NF135 and the NF166 cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments here suggest that qRT-PCR has lower intra- and inter-assay variation compared to QT-NASBA. The higher precision of qRT-PCR is evident for the entire range of gametocyte densities used in the dilution series, despite involving extra reaction steps, such as DNase treatment and cDNA production, which are known to be a source of variation [27]. These two steps were performed once for each dilution series density, for the three different NF54 cultures and the NF135 and the NF166 cultures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the results of the RT depended on the characteristics of the RT enzyme, samples, RNA concentrations and assays [88]. …”
Section: Normalization Quality Control and Reportingmentioning
confidence: 99%
“…Yet another paper reported gene-related factors as the primary determinants of RT variability and called for an evaluation of the RT robustness of control genes in RT-qPCR normalisation [40]. A recent paper has demonstrated that the fold changes reported by most RNA biomarkers are well within the range of variability observed when multiple RT reactions are carried out on the same template [41]. The conclusions from these papers are rather stark and place question marks behind many of the results reported not just in the biomedical literature but in the scientific literature as a whole.…”
Section: Technical Issuesmentioning
confidence: 99%